Characterizing fluid flow paths in the Hellisheidi geothermal field using detailed fault mapping and stress-dependent permeability. (July 2021) - Mahzari, Pedram; Stanton-Yonge, Ashley; Sanchez-Roa, Catalina; Saldi, Giuseppe; Mitchell, Thomas; Oelkers, Eric H.; Hjorleifsdottir, Vala; Snaebjornsdottir, Sandra Osk; Ratouis, Thomas; Striolo, Alberto; Jones, Adrian P.
Highlights: High-resolution drone imaging of fracture network for Hellisheidi reservoir. Dual porosity model for fluid flow path constructed. Stress-dependent permeability used for modeling. Batch and continuous tracer injections were reproduced by the model. The impact of stress-dependent permeability is crucial in fracture reservoir characterization.. Abstract: The Husmuli zone of the SW-Iceland Hellisheidi geothermal field is currently being used for re-injection of geothermal fluids and geothermal CO2 for its permanent storage in the form of carbonate minerals. A fully coupled hydro-thermo-mechanical numerical model was employed to investigate the coupled impacts of these complex processes on the calibration of fluid flow paths, which can have significant implications for the long-term performance of this subsurface reservoir. Employing a combination of high-resolution fault mapping with laboratory measurements of stress dependent permeability coupled into a dual porosity field-scale model, the flow paths were calibrated using results of tracer tests performed at the site using stress-dependent permeability tensors. Although vertically extended faults are the primary fluid flow paths, fractures connecting the faults can play an important role in fluid transport. As the upward flow streamlines manifest, deep geological layers can also deviate the fluid flow towards the shallower layers provoking the vertical flow of geothermal fluids. This highlights the sweet spot for sustainable flow and heat extraction in vicinity of faults intercepting the geological layers at depth of 1100 m. It was also shown that the inclusion of the geomechanical calculations in the history matching of the tracer test could lead to changes in arrival time and peak of the tracer profiles. Results of an independent tracer test were used to validate the model and to demonstrate the predictive capability of the calibrated model. This verifies the consistency of our methodology to incorporate the stress-dependent permeability. The results of this comprehensive modelling study provide insight into the likely fluid flow paths, which can have profound impact on the evaluation of various processes such as CO2 mineralisation taking place in Hellisheidi geothermal reservoir.